Penyuluhan Mengenai Gangguan Kognitif dan Pengalaman Positif Caregiving pada Pengasuh Penderita Demensia - Sri Budhi Rianawati; Herpan Syafii Harahap; Neila Raisa; Dwi Atri, Ausi Mutiara; Wa Ode Nur Intan Octina (Universitas Mataram, 2025)
This community service activity was organized by the Neurology Department of Brawijaya University in collaboration with the Neurology Department of Mataram University. The event included a health education session on cognitive disorders, delivered both offline at the Neurology Polyclinic of RSUD dr. Saiful Anwar Malang and online via Zoom and YouTube. Participants were introduced to dementia screening using the SINARSIS web-based application. Through this socialization, we hope that the community will find it easier to identify cognitive disorders by using the SINARSIS application for screening. The activity consisted of pre- and post-tests, educational material delivery, discussions, and the administration of the Positive Aspects of Caregiving (PAC) questionnaire. A total of 98 participants from Malang and Mataram attended the Zoom session, while 45 attended the offline session. Among the participants, 74 were caregivers of dementia patients. The high level of engagement was evident from the documentation and the improvement in the post-test scores compared to the pre-test. The activity demonstrated its effectiveness in enhancing participants’ understanding of memory loss in dementia patients. Additionally, the results from the PAC questionnaire indicated a positive shift in caregivers' attitudes and behaviors toward caring for individuals with cognitive impairments. Keywords: Cognitive Function; Web-based Application; Screening; Caregiver